AN EFFICIENT PROTOCOL FOR GENOMIC DNA ISOLATION FROM CULTIVABLE BACTERIA - PAVAN KUMAR PINDI; RAJA SRINATH R; A. SHIVA SHANKER (International Journal of Pharma and Bio Sciences, 2013)
A standardized protocol can play a major role in isolation of DNA especially when dealing with bacterial cultures. The aim of the present study was to develop a standard protocol of ultrapure high yield bacterial genomic DNA extraction from bacterial culture suitable for use in molecular biology. Extraction procedure was optimized with series of steps, which involved an unpublished modification of an alkaline lyses procedure followed by equilibrium ultracentrifugation incubated in a lysozyme, buffer and treated with alkaline detergent. Detergent solubilizes proteins and membrane proteins are precipitated with sodium acetate, and the lysates was clear. The cleared lysate with further more steps likewise spooling, phenol: chloroform: isoamyl alcohol and ethanol purification of DNA will give a very high yield, purified bacterial DNA when compared to already existing methods. This method describes the recovery of highly purified nucleic acids that are well-suited for molecular purposes even though a new challenge concerns the recovery of large bacterial DNA essential for functional investigation of gene clusters and biosynthetic pathways.